Aktivitas Antialopesia Sediaan Hairtonic Dari Berbagai Tanaman - Arum Hasanah; Dikdik Caesar Barkah; Dinda Aisyah; Nia Yuniarsih (Syntax Corporation Indonesia, 2022)
Hair is a part of the body that is often referred to as a crown by every human being given by God. However, problems that can occur in hair if not treated properly can cause one of them is hair loss. Hair loss is a major problem, in appearance. Because having healthy and beautiful hair can increase a person's confidence in appearance. The use of hair tonic today is a must if it is to prevent or repair hair damage, because hair tonic is a liquid cosmetic preparation consisting of chemicals and/or other ingredients that can be used to help repair, strengthen and maintain hair condition. hair tonic is a product for the treatment of hair loss that is safe and does not cause irritation. Various plant extracts are formulated to treat hair loss as an alternative to synthetic hair tonics which can cause side effects. Therefore, this review article aims to inform various kinds of plants that can be used as ingredients for making hair tonic cosmetic preparations. The results of the study of the article show that in various plant parts of plants that have the potential as anti-alopecia for hair tonic preparations are bidara leaves, kukukan leaves, celery leaves, hibiscus flowers and candlenut by showing the effectiveness of hair growth and preventing hair loss within a period of 4-8 days. week.